Analisis Instrumen Spektra FTIR Dan GC-MS Senyawa Kalkon Hasil Sintesis dari Vanilin dalam Majalah Kimia: Suplemen Perkuliahan Kimia Organik Lanjut - Rahmawati, Rahmawati; Sudianti, Dini; Al Idrus, Syarifa Wahidah (FKIP University of Mataram, 2025)
This study aims to analyze chalcone compound instruments and develop a chemistry magazine as supplementary reading material for students. The research adopts the 4D development model, which consists of four stages: define, design, develop, and disseminate. The magazine was validated by three lecturers from the Chemistry Education and FMIPA study programs, while student response testing was conducted on 47 Chemistry Education students at the University of Mataram. The validation results using Aiken’s V index indicate a score of 0.83, categorized as highly valid. Additionally, the magazine's feasibility level reached 90.03%, classified as highly practical. Therefore, this chemistry magazine is suitable as supplementary reading material in chemistry learning.